Reciprocal recursive nonconscious behavior mimicry, PE groupings, and modification-by-adaptation. Issue 2 (3rd May 2020) - Rhoades, Jesse Lee; Hopper, Timothy
ABSTRACT: This manuscript outlines the possible benefits of nonconscious behavioural mimicry (NBM) to Physical Education (PE). The identification of NBM as an unexamined phenomenon in PE will be explored, as well as factors mediating its occurrence. Further, this manuscript will discuss the speculated origins of this phenomenon within the human species. Drawing on ecological cognition, this paper seeks to explain how students in PE could benefit from NBM in mixed ability groupings within adaptive environmental constraints. Describing a volleyball example using teaching strategies informed by both Teaching Games for Understanding and the Sport Education Model, the authors propose possible benefits and applications of this phenomenon in game-based PE lessons.